Europe as a Stronger Global Actor : Challenges and Strategic Responses - Duke, Simon (Palgrave Macmillan UK Imprint: Palgrave Macmillan, 2020)
ontents: Introduction -- Chapter 1. The EU’s strategic unconsciousness and normative hubris -- Chapter 2. Existential doubts and Strategic dilemmas -- Chapter 3. In search of strategy -- Chapter 4. The return of geopolitics and relations to the east -- Chapter 5. Geopolitics in the post-Arab Spring -- Chapter 6. Transatlantic relations and Europe’s missing Asia pivot -- Chapter 7. Europe’s harder edges: Security and Defence -- Chapter 8. Putting effectiveness into multilateralism -- Chapter 9. Strategy, implementation and means -- Chapter 10. Reconceptualizing the world and the liberal delusion. .